A Prospective 2-Year Examination of Cognitive and Behavioral Correlates of Provoked Vestibulodynia Outcomes. Issue 4 (April 2015) - Davis, Seth N. P.; Bergeron, Sophie; Bois, Katy; Sadikaj, Gentiana; Binik, Yitzchak M.; Steben, Marc
<x xml:space="preserve">Abstract</x> Background: Provoked vestibulodynia (PVD) is a common genital pain disorder in women that is associated with sexual dysfunction and lowered sexual satisfaction. A potentially applicable cognitive-behavioral model of chronic pain and disability is the fear-avoidance model (FAM) of pain. The FAM posits that cognitive variables, such as pain catastrophizing, fear, and anxiety lead to avoidance of pain-provoking behaviors (eg, intercourse), resulting in continued pain and disability. Although some of the FAM variables have been shown to be associated with PVD pain and sexuality outcomes, the model as a whole has never been tested in this population. An additional protective factor, pain self-efficacy (SE), is also associated with PVD, but has not been tested within the FAM model. Aims: Using a 2-year longitudinal design, we examine (1) whether initial levels (T1) of the independent FAM variables and pain SE were associated with changes in pain, sexual function, and sexual satisfaction over the 2-year time period; (2) the prospective contribution of changes in cognitive-affective (FAM) variables to changes in pain, and sexuality outcomes; and (3) whether these were mediated by behavioral change (avoidance of intercourse). Methods: A sample of 222 women with PVD completed self-report measures of FAM variables, SE, pain, sexual function, and sexual satisfaction at time 1 and at a 2-year follow-up. Structural equation modeling with Latent Difference Scores was used to examine changes and to examine mediation between variables. Main Outcomes: Questionnaires included the Pain Catastrophizing Scale, McGill Pain Questionnaire, Trait Anxiety Inventory, Pain Self-Efficacy Scale, and Global Measure of Sexual Satisfaction, Female Sexual Function Index. Results: Participants who reported higher SE at T1 reported greater declines in pain, greater increases in sexual satisfaction, and greater declines in sexual function over the 2 time points. The overall change model did not support the FAM using negative cognitive-affective variables. Only increases in pain SE were associated with reductions in pain intensity. The relationship between changes in SE and changes in pain was partially mediated through changes in avoidance (more intercourse attempts). The same pattern of results was found for changes in sexual satisfaction as the outcome, and a partial mediation effect was found. There were no significant predictors of changes in sexual function other than T1 SE. Discussion: Changes in both cognitive and behavioral variables were significantly associated with improved pain and sexual satisfaction outcomes. However, it was the positive changes in SE that better predicted changes in avoidance behavior, pain, and sexual satisfaction. Cognitive-behavior therapy is often focused on changing negative pain-related cognitions to reduce avoidance and pain, but the present results demonstrate the potential importance of bolstering positive self-beliefs as well. Indeed, before engaging in exposure therapies, SE beliefs should be assessed and potentially targeted to improve adherence to exposure strategies.